Innovation in Acid Mine Drainage Remediation Using Coffee Waste Biochar in Michiquillay, 2025 - Licapa-Redolfo, Gladys Sandi; Camino Romero, Maria Jesus; Gomez Gonzales, Renzo Brandon Joel (LACCEI, 2025)
This research aims to remove heavy metals from Acid Mine Drainage (AMD) using activated carbon from coffee waste. To do this, 0.5 g, 1 g, and 1.5 g of biochar were applied in triplicate in 250 mL beakers each; the tests were conducted at 15-minute intervals for a total time of one hour. The results showed the initial presence of copper (3.9185 mg/L), zinc (18.2 mg/L), and iron (0.215 mg/L); after the treatment process, the final concentrations were 0.0155 mg/L, 1.49833 mg/L, and 0.0309 mg/L, respectively. Additionally, an increase in the average pH was recorded from 4.77 to 7.67, achieving a neutral pH. These results demonstrate that coffee biochar, due to its high porosity when activated, has a remarkable absorption capacity. Ultimately, 99% copper, 85% zinc, and 91% iron were removed, confirming the high efficiency of this activated agroindustrial waste and meeting Environmental Quality Standards.